Le masque comme sujet : la matérialité du masque, entre forme, usage et savoir-faire - MOISE, Candice (Studia Universitatis Babeș-Bolyai Dramatica, 2025)
The paper The Mask as Subject: the Materiality of the Mask, between Form, Use, and Craftsmanship examines the object mask as a subject, utilised in both live performance and traditional European festivals. The analysis focuses on the ergonomics of masks and their relationship to the body, distinguishing between different types of wear and their expressive implications. The article explores the treatment of eye and mouth openings, revealing the technical choices that determine the character’s expression. An analysis of materials and manufacturing methods reveals a dichotomy between the preservation of traditional skills and the pursuit of technical innovation. This material approach to the mask, which extends beyond the conventional symbolic analyses, facilitates an understanding of how communities engage in the negotiation of their relationship with tradition. In this regard, the mask assumes the role of a mediator between permanence and change, between the physical body and its representation.